Rent-a-girlfriend. Volume 3 - Miyajima, Reiji (Kodansha Comics, 2020)
"You can rent a girlfriend, but can you buy love? Reeling from a bad breakup, Kazuya rents the beautiful, polite Chizuru for a date. But rock bottom might be so much lower than he thought! Chizuru is much more than the pretty face and sweet demeanor he thought he'd bargained for ... IN HOT WATER Kazuya's maritime heroics have complicated his decision to completely cut ties with his rental girlfriend, Chizuru. Now the stage is set for a different kind of conversation ... Chizuru has always bailed him out of his cowardly ways and awkward encounters, but how will she react after he saves her life?"--Provided by publisher